Enhancing Speaking Skills through Peer Tutoring in Language Learning ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Peer tutoring is a collaborative learning strategy where students assist each other in mastering academic content or skills. This article explores the use of peer tutoring to enhance speaking skills in language learning contexts. By engaging learners as both tutors and tutees, peer tutoring promotes speaking fluency, confidence, and accuracy through interactive practice and feedback exchange. The article discusses theoretical foundations, benefits, practical strategies, and case studies demonstrating the effectiveness of peer tutoring in fostering speaking proficiency and supporting language development.